Association between postural awareness, sedentary behaviour, and back pain during the hybrid study among undergraduate students - Low, Xin Yuen (2022)
Background and Objective: Low back pain is one of the most prevalent health issues affecting individuals of all ages, including children and the elderly. Approximately 85% of people have experienced it at least once in their lives. Thus, the low back pain issue should be addressed, and its associated factors, which are postural awareness and sedentary behaviour should be studied thoroughly. Hence, this study aims to investigate the association between postural awareness, sedentary behaviour, and back pain during the hybrid study among undergraduate students. Methods: This is a cross-sectional quantitative design study. A self-reported questionnaire was distributed to undergraduate students in UTAR Sungai Long and Kampar campuses through Google Forms. The Postural Awareness Scale, Sedentary Behavior Questionnaire, and The Quebec Back Pain Disability Scale were utilized to examine the participants’ postural awareness level, sedentary behaviour, and back pain, respectively. Results: Data from 390 participants were analyzed. Spearman’s rho test revealed no significant association between postural awareness (p = 0.747) and back pain (p = 0.747) during the hybrid study among undergraduate students. Besides that, no significant association was found between sedentary behaviour (p = 0.339) and back pain (p = 0.339) during the hybrid study among undergraduate students. Conclusion: There is no significant association between postural awareness, sedentary behaviour, and back pain during the hybrid study among undergraduate students. This may be because back pain can be due to other risk factors such as gender, age, faculty, year of study, smoking, drinking alcohol, physical activity level, etc. In order to avoid this catastrophe, the government, general public, school administration, parents, and students should put in place some preventative measures.